Pengaruh Pengembangan Karir dan Kompensasi Terhadap Turnover Intention Pada Generasi Z di Indonesia - Muhammad Abi Ikhwanudin; Puspita Wulansari (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the influence of career development and compensation on turnover intention among Generation Z in Indonesia. The high turnover intention phenomenon within Generation Z has impacted company sustainability. This study examines the relationship between career development, compensation, and the intention to leave a job among young workers. The research employed a quantitative descriptive approach, surveying 215 respondents. The variables studied included career development, compensation, and turnover intention. Data analysis was conducted using the SEM-PLS method to test the relationships between variables. The results revealed that career development and compensation, both partially and simultaneously, do not significantly influence turnover intention. Neither optimal nor inadequate career development and compensation affect employees' intentions to leave their jobs. In conclusion, companies should consider other factors, such as organizational culture or work-life balance, to better understand turnover intention among Generation Z. This study provides theoretical and practical contributions and recommends further exploration of other influencing factors.